Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jora.12192
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Generational Status, and Parent–Adolescent Sexual Communication: Implications for Latino/a Adolescent Sexual Behavior

Abstract: There is little research on how specific parent-adolescent sexual communication topics influence Latino/a youth’s sexual behaviors, and how gender and generational status may moderate effects. This study examined effects of three different messages on intercourse and condom use among 1944 Latino/as from the National Longitudinal Study of Adolescent Health (T1 mean age=15.46; sd=1.50). Results indicated discussing health consequences predicted higher odds of intercourse one year later across gender and generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 80 publications
5
36
0
Order By: Relevance
“…Although women in the first generation had more sexual partnerships in the last year as compared to women in the third generation, the greater use of condoms by women in the first generation, likely reduces their experience of STIs (Pflieger et al, 2013). Our findings are consistent with Deutsch and Crockett’s (2015) finding that immigrants are more likely to use a birth control method in sexual partnerships than nonimmigrants. Restrictive norms about non-marital sexual activities among immigrant populations (Kim & Ward, 2007) may reduce first generation women’s risk-taking in sexual relationships.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although women in the first generation had more sexual partnerships in the last year as compared to women in the third generation, the greater use of condoms by women in the first generation, likely reduces their experience of STIs (Pflieger et al, 2013). Our findings are consistent with Deutsch and Crockett’s (2015) finding that immigrants are more likely to use a birth control method in sexual partnerships than nonimmigrants. Restrictive norms about non-marital sexual activities among immigrant populations (Kim & Ward, 2007) may reduce first generation women’s risk-taking in sexual relationships.…”
Section: Discussionsupporting
confidence: 92%
“…Restrictive norms about non-marital sexual activities among immigrant populations (Kim & Ward, 2007) may reduce first generation women’s risk-taking in sexual relationships. Our findings for young adult women extend findings from past research on adolescents showing that foreign-born adolescents engage in less sexual risk taking than the native-born (Becker et al, 2014; Deutsch & Crockett, 2015; Guarini et al, 2015; Hussey et al, 2007; Karoly et al, 2015). …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study found sexual communication with only fathers to predict a decreased likelihood of both primary and secondary abstinence. Fathers probably engage in discussions about sex with their youth when they suspect the youth have become sexually active [27]. The sexual activity may therefore have preceded the communication with fathers.…”
Section: Discussionmentioning
confidence: 99%
“…But the evidence on the relationship between sexual communication and abstinence is inconclusive. While some studies find parental sexual communication to be associated with a higher likelihood of abstinence [25,26], others find the reverse [27,28]. Many of the studies on sexual communication also focus on mothers [28][29][30][31], while paying less attention to the effect of communicating with fathers and friends.…”
Section: Introductionmentioning
confidence: 99%